Narcissism and Workplace Stress: A Cross-sectional Comparative Study among Healthcare and Non-Healthcare Professionals - K. Ganesh Kini; Tanisha S. Bhat; Ravichandra Karkal (Journal of Psychiatry Spectrum, 2025)
Background: Narcissism as a personality trait is poorly understood due to its heterogeneous nature and has a negative connotation associated with it. However, there are studies indicating a negative correlation between narcissism and workplace stress. Aims: The aim is to investigate the association between narcissism and workplace stress among healthcare and non-healthcare professionals. Materials and Methods: Through purposive sampling 230 participants were recruited, i.e., 115 in each of the two arms (healthcare and non-healthcare professionals) of the study. Narcissism and workplace stress were measured using the Narcissistic Personality Inventory-16 and the Workplace Stress Scale, respectively. Results: Healthcare professionals had a statistically significant (U = 5375, P < 0.013), lower narcissism score compared to non-healthcare professionals (Mean = 3.12 [standard deviation (SD) = 2.59] vs. Mean 4.07 [SD = 3.02]). Whereas healthcare professionals reported a statistically significant (t = 3.29, df = 219, P < 0.001), higher workplace stress score compared to non-healthcare professionals (Mean = 22.3 [SD = 6.90] vs. Mean = 19.5 [SD = 5.64]). However, there was no statistically significant correlation between narcissism and workplace stress in correlation analysis (Spearman’s ρ = −0.038, P = 0.284). Conclusion: Although there are significant differences in narcissism and workplace stress between healthcare workers and non-healthcare professionals, the relationship between the two variables remains inconclusive. Future research should examine, with a balanced view, the adaptive and maladaptive traits of narcissism to better understand its role in mitigating workplace stress and its broader effects on professional relationships.